Gallium nitride powder and method for producing the same
By controlling the electrical properties and particle size of gallium nitride powder through heat treatment, high compaction densities are achieved, addressing the limitations of pressurized sintering and enabling the production of sintered bodies for sputtering targets.
Patent Information
- Application Number
- JP2024048784
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-09
- Filing Date
- 2024-03-25
- Publication Date
- 2024-12-19
AI Technical Summary
Conventional methods for producing gallium nitride sintered bodies using pressurized sintering face limitations in shape control and require large-scale equipment, and gallium nitride powder exhibits poor formability, making it difficult to achieve high compaction densities in molded compacts.
A gallium nitride powder with controlled electrical properties, oxygen content, and particle size distribution is produced through heat treatment, enabling high compaction densities without pressurized firing, using a method that includes heat treatment at specific temperatures in an inert gas atmosphere.
The method yields a compact with higher compaction density and moldability, allowing for the production of sintered bodies suitable for sputtering targets and other applications without the need for pressure firing.
Smart Images

Figure 2024177063000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to gallium nitride powders, and in particular to gallium nitride powders suitable as precursors for sputtering targets. [Background technology]
[0002] Conventionally, gallium nitride (GaN) sintered bodies have been produced by pressure firing such as hot pressing, which simultaneously molds and fires (sinters) gallium nitride powder. Pressure firing requires a large-scale device, and the shape of the resulting gallium nitride sintered body is limited. Therefore, a method for producing a gallium nitride sintered body without pressure firing is required. However, gallium nitride has low moldability, and it is difficult to mold (make a powder compact) prior to firing. Therefore, gallium nitride powder that can provide a molded body prior to firing is being studied. For example, Non-Patent Document 1 reports that a gallium nitride molded body can be obtained by controlling the particle size of the powder by pulverizing it with a jet mill. [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] Journal of Crystal Growth 208 (2000) 100-106 Summary of the Invention [Problem to be solved by the invention]
[0004] The gallium nitride powder disclosed in Non-Patent Document 1 could be molded, but the resulting compact had a low relative density of 60%, and furthermore, the compact tended to cleave, making it difficult to maintain a stable shape as a compact.
[0005] An object of the present disclosure is to provide at least one of a gallium nitride powder that can produce a compact with a higher compact density than conventional gallium nitride powders, a method for producing the same, and a method for producing a sintered body using the same. [Means for solving the problem]
[0006] In this disclosure, in order to obtain a gallium nitride sintered body suitable for a sputtering target without pressure sintering, we have investigated the preparation of a gallium nitride compact prior to sintering. As a result, we have found that a compact with high compact density can be obtained by focusing on the electrical properties of the powder and controlling these within a specific range.
[0007] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] Gallium nitride powder with an oxygen content of 0.5 at% or less, and which has an electrical resistivity of 1.0 x 10 when 8 g of the powder is filled into a 10 mm x 40 mm rectangular mold and uniaxially pressed at a pressure of 100 MPa. 7 Gallium nitride powder with a resistivity of less than Ω·cm. [2] The powder according to the above [1], wherein the gallium nitride is gallium nitride having nitrogen defects. [3] The powder according to [1] or [2] above, having a loose bulk density of 1.00 g / mL or more and 1.85 g / mL or less. [4] The powder according to any one of [1] to [3] above, having an average particle size of 1 μm or more and 150 μm or less. [5] The powder according to any one of [1] to [4] above, wherein the 10% area diameter to the 90% area diameter is 0.01 or more and 0.45 or less. [6] A method for producing the powder according to any one of [1] to [5] above, comprising a heat treatment step of heat treating gallium nitride powder at 900°C or higher and 1300°C or lower in an inert gas flow atmosphere. [7] The method according to [6] above, wherein the gallium nitride powder is gallium nitride powder obtained by nitriding metallic gallium. [8] The manufacturing method according to [6] or [7] above, wherein the inert gas flow atmosphere is an atmosphere in which a gas containing at least one of argon and nitrogen is flowed. [9] The method for producing a gas according to any one of [6] to [8] above, wherein the flow rate of the inert gas is 500 mL / min or more and 5000 mL / min or less.
[10] A method for producing a sintered body of gallium nitride, comprising the steps of: forming a powder according to any one of the above items [1] to [5] into a molded body; and sintering the molded body. Effect of the Invention
[0008] The present disclosure makes it possible to provide at least one of a gallium nitride powder that can give a compact with a higher compact density than conventional gallium nitride powders, a method for producing the same, and a method for producing a sintered body using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The powder of the present disclosure will be described below with reference to an example of an embodiment. In this disclosure, "at%" is synonymous with "atm%" and is a unit expressing a ratio based on the number of atoms. In addition, this disclosure includes any combination of the configurations and parameters disclosed in this specification, and also includes any combination of the upper and lower limits of the values disclosed in this specification.
[0010] The powder of this embodiment is a gallium nitride powder having an oxygen content of 0.5 at% or less, and when 8 g of the powder is filled into a rectangular parallelepiped mold of 10 mm × 40 mm and uniaxially press-molded at a pressure of 100 MPa, the electrical resistance is 1.0 × 10 7 Gallium nitride powder has a resistivity of less than Ω·cm.
[0011] The powder of this embodiment may be any powder containing gallium nitride (GaN) as the main component (matrix), that is, a powder essentially made of gallium nitride, and may contain unavoidable impurities.
[0012] The oxygen content of the powder of this embodiment is 0.5 at% or less, and preferably 0.4 at% or less or 0.3 at% or less. If the oxygen content exceeds 0.5 at%, a gallium oxide layer is formed, resulting in high electrical resistivity. It is preferable that the oxygen content is low, for example, 0.02 at% or more or 0.05 at% or more. A preferred oxygen content is 0.02 at% or more and 0.5 at% or less, or 0.05 at% or more and 0.3 at% or less.
[0013] In this embodiment, the oxygen content is the atomic ratio [at%] of oxygen in the powder relative to the gallium nitride powder, and is a value calculated from the value [mass%] measured by an inert gas fusion-infrared absorption method using an oxygen / nitrogen analyzer (e.g., LECO ON736, manufactured by Leco) using the following formula (1): Oxygen content [at%] =(W O / M O ) / {(W Ga / M Ga )+(W N / M N )+(W O / M O )} (1)
[0014] In equation (1), M O is the atomic weight of oxygen (16.00 [g / mol]), M Ga is the atomic weight of gallium (69.72 [g / mol]), and M N is the atomic weight of nitrogen (14.01 [g / mol]). O and W N is a value [mass %] measured by inert gas fusion-infrared absorption method using an oxygen / nitrogen analyzer (e.g., LECO ON736, manufactured by Leco). Ga is W O and W N This value is calculated from the measured values using formula (2). 100=W Ga [Mass%]+W O [Mass%]+W N [Mass%] (2)
[0015] The powder of this embodiment has an electrical resistivity of 1.0×10 when 8 g of the powder is filled into a rectangular parallelepiped mold of 10 mm×40 mm and uniaxially pressed at a pressure of 100 MPa (hereinafter, simply referred to as "electrical resistivity"). 7 Ω·cm or less. By combining the electrical resistivity and the oxygen content described above, the powder of this embodiment has high moldability, and a molded body can be obtained without sintering. One of the reasons why the powder of this embodiment exhibits excellent moldability is thought to be the following. That is, by combining the oxygen content and electrical resistivity of the powder of this embodiment, the powder particles repel each other appropriately, making it difficult for local aggregation to occur. On the other hand, it is thought that the powder particles tend to become dense when an external force is applied, and as a result, the powder exhibits excellent moldability.
[0016] Since the lower the electrical resistivity, the higher the formability tends to be, the electrical resistivity is set to 1×10 5 Ω·cm or less, 1Ω·cm or less or 1×10 -1 The electrical resistivity is preferably less than 1×10 ―4 Ω cm or more or 1×10 ―3 The preferred electrical resistivity is 1×10 -4 Ω cm or more 1×10 7 Ω cm or less, 1×10 -3 Ω cm or more 1×10 5 Ω cm or less or 1×10 -4 Ω cm or more 1×10 -1 An example would be Ω·cm or less.
[0017] In this embodiment, the electrical resistivity of the powder is a value measured by the following method. That is, 8 g of the powder is filled into a rectangular parallelepiped mold of 10 × 40 mm, and molded by uniaxial pressing at a pressure of 100 MPa to obtain a molded body for evaluation. The electrical resistivity of the molded body for evaluation may be measured using a general resistivity meter (for example, Loresta-GX MCP-T700, manufactured by Nitto Seiko Analytech Co., Ltd.) and a TFP probe as a measurement probe.
[0018] Since the gallium nitride in the powder of this embodiment is likely to have such an electrical resistivity, it is preferable that the gallium nitride in the powder of this embodiment is a powder made of gallium nitride having nitrogen defects, that is, so-called nitrogen-deficient gallium nitride.
[0019] In addition to being highly moldable, the powder of this embodiment preferably has high packing properties during handling, such as transportation. In order to facilitate such packing properties, the loose bulk density of the powder of this embodiment may be 1.00 g / mL or more, 1.30 g / mL or more, or 1.50 g / mL or more. In addition, the loose bulk density is preferably high, but examples of the loose bulk density include 1.85 g / mL or less, 1.80 g / mL or less, or 1.70 g / mL or less, and it is preferably 1.00 g / mL or more and 1.85 g / mL or less, 1.30 g / mL or more and 1.85 g / mL or less, or 1.50 g / mL or more and 1.70 g / mL or less.
[0020] The loose bulk density may be measured by a method conforming to JIS Z 2504. That is, in this embodiment, the loose bulk density may be measured by the following method. That is, a funnel with an orifice diameter of 2.5 mm and a funnel angle of 60° is used, and the powder is poured into a funnel with an inner diameter of 28 mm and a volume of 25 cm. 3 The powder is poured into a cylindrical container of 25 cm3, and the powder pouring is stopped when the cylindrical container is filled with powder. After the powder is poured, the surface of the cylindrical container is scraped without applying compression or vibration. The volume of the cylindrical container [25 cm3] is 3 The mass of the powder after leveling [g] relative to the total mass [g] of the powder is the loose bulk density.
[0021] The average particle size of the powder of this embodiment is 1 μm or more, or 2 μm or more, and may be 150 μm or less, 50 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. Preferred average particle sizes include 1 μm or more and 150 μm or less, 2 μm or more and 50 μm or less, 2 μm or more and 20 μm or less, or 2 μm or more and 10 μm or less. By having such an average particle size, the amount of oxygen is not too large, and moldability is easily improved.
[0022] In this embodiment, the average particle diameter is a value determined from the area of primary particles observed in an SEM observation image obtained using a general scanning electron microscope (e.g., VE-9800, manufactured by KEYENCE Corporation; hereinafter, also referred to as "SEM") under the following conditions: Accelerating voltage: 10kV Observation magnification: 50 to 5000 times
[0023] The obtained SEM observation image is binarized and analyzed using a general image analysis software (e.g., Image-Pro10), 1200±400 primary particles whose outlines are observed without interruption in the SEM observation image are extracted, and the longest diameter of each primary particle is measured and this is regarded as the particle diameter of each primary particle. The average particle diameter can be determined by averaging the particle diameters of each primary particle.
[0024] Since the moldability is easily improved, it is preferable that the primary particles of the powder of this embodiment have a moderate particle size distribution. For example, it is preferable that the ratio of the 10% diameter (D10) [μm] to the 90% diameter (D90) [μm] is 0.01 or more and 0.45 or less, and more preferably 0.04 or more and 0.20 or less.
[0025] In this embodiment, D10 and D90 are obtained by calculating the area of a circle having the longest diameter as a diameter from the longest diameter (particle diameter) of each primary particle obtained by a method similar to that for measuring the average particle diameter, and the longest diameters corresponding to the areas of circles corresponding to 10% and 90% of the cumulative area are defined as D10 and D90, respectively.
[0026] The powder of this embodiment can be molded without using molding that accompanies sintering, such as pressure sintering.
[0027] The powder of this embodiment has high moldability. For example, when 8 g of the powder is filled into a rectangular parallelepiped die of 10 mm × 40 mm and uniaxially press molded at a pressure of 100 MPa, the measured density (hereinafter also referred to as "molded density") is 2.0 g / cm. 3 More than 3.0g / cm 3 More than 3.5g / cm 3 More than 3.8g / cm 3or more than 4.0g / cm 3 The higher the molding density, the better, but it is 5.0 g / cm 3 Below 4.5g / cm 3 Below, 4.2g / cm 3 or less than 4.1g / cm 3 The following are listed: 2.0g / cm 3 More than 5.0g / cm 3 Below 3.0g / cm 3 More than 4.5g / cm 3 Below 3.5g / cm 3 More than 4.5g / cm 3 Below, 3.8g / cm 3 More than 4.5g / cm 3 Below 3.5g / cm 3 More than 4.2g / cm 3 Less than or equal to 4.0g / cm 3 More than 4.1g / cm 3 The following are some of the reasons:
[0028] In addition, the powder of this embodiment has a flexural strength (hereinafter also referred to as "flexural strength of molded body") of 2.1 MPa or more, 2.3 MPa or more, or 2.5 MPa or more when 8 g of the powder is filled into a rectangular parallelepiped mold of 10 mm x 40 mm and uniaxially press molded at a pressure of 100 MPa. The higher the flexural strength of the molded body, the more preferable it is, and examples of the flexural strength include 10 MPa or less, 8 MPa or less, 7.0 MPa or less, 5.0 MPa or less, 4.5 MPa or less, or 4.0 MPa or less, and examples of the flexural strength include 2.1 MPa or more to 10 MPa or less, 2.3 MPa or more to 7 MPa or less, 2.5 MPa or more to 5.0 MPa or less, or 2.5 MPa or more to 4.0 MPa or less.
[0029] The powder of the present embodiment can be used for known applications of gallium nitride powder, and is particularly preferably used as a precursor for a sintered body, a precursor for a sintered body for a sputtering target, and further as a precursor for a polycrystalline gallium nitride substrate.
[0030] Next, a method for producing the powder according to this embodiment will be described.
[0031] The powder of this embodiment may be produced by any method as long as the powder of gallium nitride having the above-mentioned configuration can be obtained. A preferred production method includes a method for producing a powder having a heat treatment step of heat treating the gallium nitride powder in an inert gas flow atmosphere at 900°C to 1300°C.
[0032] The gallium nitride powder (hereinafter also referred to as "raw material powder") to be subjected to the heat treatment step is preferably gallium nitride powder obtained by nitriding metal gallium.
[0033] The metallic gallium to be subjected to the nitriding treatment may be any commercially available metallic gallium, and an example of the metallic gallium is metallic gallium with a purity of 3N or more and 7N or less.
[0034] The nitriding treatment may be carried out under conditions that allow the nitridation of metallic gallium to proceed, and examples of the conditions include the following. Nitriding atmosphere: Nitrogen-containing gas flow atmosphere, Preferably, the atmosphere is a nitrogen or ammonia flow atmosphere. More preferably, an ammonia flow atmosphere Nitriding temperature: 900℃ to 1100℃ Preferably, 950°C or higher and 1050°C or lower Heating rate: 5℃ / min to 50℃ / min Preferably, 8°C / min to 20°C / min
[0035] The nitriding time may be appropriately adjusted depending on the metallic gallium used in the nitriding treatment and the nitriding method, and may be, for example, from 30 minutes to 15 hours, or from 1 hour to 10 hours.
[0036] In the heat treatment step, the raw material powder is heat treated at 900°C to 1300°C in an inert gas flow atmosphere. This is believed to cause gallium nitride to be appropriately thermally decomposed, resulting in part of the nitrogen being eliminated to form nitrogen-deficient gallium nitride, which then forms conductive carriers. This results in the powder of the present embodiment having an electrical resistivity that contributes to improving moldability.
[0037] In the heat treatment step, the heat treatment is performed in an inert gas atmosphere. This prevents the oxygen content of the resulting powder from excessively increasing. The inert gas atmosphere may be any atmosphere in which oxidation of the raw material powder does not proceed, and is preferably an atmosphere in which at least one of argon and nitrogen is circulated, and more preferably a nitrogen gas atmosphere.
[0038] The flow rate of the inert gas may be any rate that suppresses scattering of the raw material powder to be treated and replaces the gas generated by the heat treatment, and may be, for example, 500 mL / min to 5000 mL / min, 800 mL / min to 4000 mL / min, or 1000 mL / min to 2500 mL / min.
[0039] The heat treatment is carried out in an inert gas flow atmosphere at 900°C or more and 1300°C or less. If the heat treatment temperature is less than 900°C, it takes a very long time for the thermal decomposition of gallium nitride, making it difficult to carry out the heat treatment in a practical time. On the other hand, if the heat treatment temperature exceeds 1300°C, the thermal decomposition of gallium nitride proceeds excessively, and the powder itself collapses. Preferred heat treatment temperatures are 950°C or more or 1000°C or more, and 1200°C or less or 1100°C or less, and are preferably 950°C or more and 1200°C or less, or 1000°C or more and 1100°C or less.
[0040] The heat treatment time may be adjusted appropriately depending on the characteristics of the heat treatment furnace, and may be, for example, from 15 minutes to 15 hours, from 30 minutes to 10 hours, or from 1 hour to 3 hours.
[0041] The heat treatment may be performed in a heat treatment furnace capable of performing heat treatment in an inert gas flowing atmosphere, and examples of the furnace include one or more selected from the group consisting of a tubular furnace, an atmospheric box-type electric furnace, and an atmospheric muffle furnace, and further includes a tubular furnace.
[0042] Next, a method for producing a sintered body using the powder of this embodiment will be described.
[0043] The powder of this embodiment can be made into a sintered body by a method similar to that of a conventional sintered body of gallium nitride, and can be used as a precursor of the sintered body of gallium nitride. As a conventional manufacturing method, there is a method of manufacturing a sintered body of gallium nitride having a step of pressurizing and sintering the powder of this embodiment. The pressurized sintering may be at least one of a hot press process and a hot isostatic press process, and is preferably a hot press process. This allows the molding and sintering of the powder to proceed simultaneously.
[0044] In addition, the powder of this embodiment has high moldability and can be molded without heating. Therefore, the powder of this embodiment is preferably used in a method for producing a gallium nitride sintered body, which includes a step of molding the powder of this embodiment to obtain a molded body, and a step of firing the molded body.
[0045] The molding method in the molding step may be any method that can obtain a molded body (green compact) of a desired shape, and may include one or more selected from the group consisting of uniaxial pressing, cold isostatic pressing, slip casting, and injection molding. Uniaxial pressing is preferred, and a molding method in which uniaxial pressing is performed at a molding pressure of 50 MPa or more and 150 MPa or less is more preferred.
[0046] The firing method in the firing step may be at least one of normal pressure firing and pressurized firing, and normal pressure firing is preferred. Note that "normal pressure firing" in this embodiment refers to a method of heating the object to be fired, such as a molded body, at a temperature equal to or higher than the temperature at which firing proceeds without applying an external force to the object to be fired.
[0047] The sintered body obtained by the manufacturing method of this embodiment can be applied to known applications of gallium nitride, and can be used for one or more selected from the group consisting of sputtering targets, gallium nitride polycrystalline substrates, and raw materials for growing single-crystal gallium nitride, and is particularly suitable as a sputtering target. EXAMPLES
[0048] The present disclosure will be described below using examples, but the present disclosure is not limited thereto.
[0049] (Electrical resistivity) The electrical resistivity of the powder was measured using Loresta-GX MCP-T700 (Nitto Seiko Analytec). That is, 8 g of the powder sample was filled into a rectangular parallelepiped mold of 10 × 40 mm, and molded by uniaxial pressing at a pressure of 100 MPa to obtain a green body for evaluation. A TFP probe was used as the measurement probe to measure the electrical resistivity of the green body for evaluation.
[0050] (flexural strength) The flexural strength of the molded product was measured in accordance with JIS R 1601 under the following conditions. Test method: Three-point bending test Distance between fulcrums: 30mm Sample size: 5 x 10 x 40 mm Head speed: 0.5mm / min
[0051] (oxygen content) The oxygen content [mass%] was measured by inert gas fusion-infrared absorption method using an oxygen / nitrogen analyzer (LECO ON736, manufactured by Leco). The oxygen content [at%] was calculated from the obtained oxygen content [mass%] and nitrogen content [mass%] using formulas (1) and (2).
[0052] (Powder X-ray diffraction) The crystal phase was measured by XRD measurement under the following conditions using a general powder X-ray diffractometer (device name: Ultima III, manufactured by Rigaku Corporation). Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: 2θ / θ scan Measurement interval: 0.01° Divergence slit: 0.5deg Receiving slit: 0.3mm Measurement time: 1.0 seconds Measurement range: 2θ=20°~80°
[0053] The crystal phase was identified by comparing the obtained XRD pattern with that in JCPDS No. 00-050-0792.
[0054] (Average particle size) The average particle size of the raw material powder was measured using a SEM (apparatus name: VE-9800, manufactured by KEYENCE Corporation) under the following conditions. Accelerating voltage: 10kV Observation magnification: 50 to 5000 times
[0055] The obtained SEM observation image was analyzed using image analysis software (Image-Pro10), and 1200±400 primary particles whose outlines were observed without interruption in the SEM observation image were extracted, and the area of each primary particle was calculated. The circle equivalent diameter was measured from the obtained area, and the average value was calculated to obtain the average particle diameter.
[0056] (Lightweight bulk density) The loose bulk density of the powder was measured by the following method. A funnel with an orifice diameter of 2.5 mm and a funnel angle of 60° was used, and the powder was poured into a funnel with an inner diameter of 28 mm and a volume of 25 cm. 3 The powder was poured into a cylindrical container of 25 cm3, and the pouring of the powder was stopped when the cylindrical container was filled with the powder. After the pouring, the surface of the powder filled in the cylindrical container was scraped off with a spatula without applying compression or vibration. The volume of the cylindrical container [25 cm3] was 3 The mass of the powder was calculated by subtracting the mass of the cylindrical container after grinding from the mass of the cylindrical container.
[0057] (Actual density) The actual density of the molded body was calculated from the mass [g] measured by an electronic balance relative to the volume [volume %] obtained from the dimensional measurement with a vernier caliper. The dimensional measurement was performed by measuring the length, width, and thickness of the rectangular solid-shaped molded body.
[0058] Example 1 30 g of metallic gallium (purity: 6N) was placed in an alumina container. After placing the metallic gallium together with the alumina container in a tubular furnace, the atmosphere was replaced with a vacuum, and a nitriding treatment was carried out under the following conditions while flowing ammonia gas, to obtain a raw material powder. Heating rate: 10℃ / min Processing temperature: 1050℃ Processing time: 2 hours
[0059] After this, the mixture was allowed to cool naturally in the tubular furnace to room temperature, and the alumina container was then recovered to obtain a raw material powder.
[0060] 30 g of the obtained raw material powder was placed in an alumina container. After placing the raw material powder together with the alumina container in a tubular furnace, the atmosphere was replaced with a vacuum, and then the raw material powder was fired under the following conditions while flowing nitrogen gas. Heating rate: 10℃ / min Firing temperature: 1000℃ Baking time: 3 hours
[0061] After firing, the mixture was allowed to cool naturally in the tubular furnace to obtain gallium nitride powder of this example.
[0062] The gallium nitride powder of this example has an oxygen content of 0.21 at%, a loose bulk density of 1.35 g / mL, and an electrical resistivity of 8.45×10 -2 The value was Ω·cm.
[0063] Example 2 Gallium nitride powder of this example was obtained in the same manner as in Example 1, except that the raw material powder was sintered under the following conditions. Heating rate: 10℃ / min Firing temperature: 1050℃ Baking time: 1 hour
[0064] The gallium nitride powder of this example has an oxygen content of 0.20 at%, a light bulk density of 1.35 g / mL, and an electrical resistivity of 2.21 × 10 -4 The value was Ω·cm.
[0065] Example 3 Gallium nitride powder of this example was obtained in the same manner as in Example 1, except that the raw material powder was sintered under the following conditions. Heating rate: 10℃ / min Firing temperature: 1000℃ Baking time: 0.5 hours
[0066] The gallium nitride powder of this example has an oxygen content of 0.20 at%, a light bulk density of 1.42 g / mL, and an electrical resistivity of 7.60×10 -1 The value was Ω·cm.
[0067] Example 4 300 g of metallic gallium (purity: 6N) was placed in an alumina container. After placing the metallic gallium together with the alumina container in a tubular furnace, the inside of the tubular furnace was evacuated, and then, while flowing ammonia gas, a nitriding treatment was performed under the following conditions to obtain a raw material powder. Heating rate: 10℃ / min Processing temperature: 1140℃ Processing time: 2 hours
[0068] After the nitriding treatment, the temperature was lowered to 1000°C at a rate of 10°C / min, then the ammonia gas was switched to nitrogen gas, and the material was fired at 1000°C for 30 minutes while flowing nitrogen gas, and then allowed to cool naturally to room temperature, obtaining the gallium nitride powder of this example.
[0069] The gallium nitride powder of this example has an oxygen content of 0.04 at%, a light bulk density of 1.71 g / mL, and an electrical resistivity of 4.24 × 10 -2 The value was Ω·cm.
[0070] Example 5 30 g of metallic gallium (purity: 6N) was placed in an alumina container. After placing the metallic gallium together with the alumina container in a tubular furnace, the inside of the tubular furnace was evacuated, and then, while flowing ammonia gas, a nitriding treatment was performed under the following conditions to obtain a raw material powder. Heating rate: 10℃ / min Processing temperature: 1125℃ Holding time: 2 hours
[0071] After the nitriding treatment, the mixture was allowed to cool naturally to room temperature in the tubular furnace to obtain a raw material powder.
[0072] 30 g of the obtained raw material powder was placed in an alumina container. After placing the metallic gallium together with the alumina container in a tubular furnace, the inside of the tubular furnace was evacuated and sintered under the following conditions while flowing nitrogen gas. Heating rate: 10℃ / min Firing temperature: 1000℃ Baking time: 3 hours
[0073] After firing, the mixture was allowed to cool naturally to room temperature, yielding gallium nitride powder of this example.
[0074] The gallium nitride powder of this example has an oxygen content of 0.07 at%, a light bulk density of 1.81 g / mL, and an electrical resistivity of 3.82 × 10 -2 The value was Ω·cm.
[0075] Comparative Example 1 The powder after the heat treatment was used as the gallium nitride powder of this comparative example. That is, 30 g of metal gallium (purity: 6N) was put into an alumina container. After placing the metal gallium together with the alumina container in a tubular furnace, the inside of the tubular furnace was evacuated, and then, while circulating ammonia gas, nitriding treatment was performed under the following conditions to obtain the gallium nitride powder of this comparative example. Heating rate: 10℃ / min Processing temperature: 1125℃ Holding temperature: 2 hours
[0076] The gallium nitride powder of this comparative example had an oxygen content of 0.19 at%, a loose bulk density of 1.89 g / mL, and an electrical resistivity of 1×10 7 It was over Ω·m.
[0077] Comparative Example 2 A commercially available gallium nitride powder (Kojundo Chemical, 4N, Lot. 302577) was used as the gallium nitride powder in this comparative example. The gallium nitride powder of this comparative example had an oxygen content of 15.50 at%, a loose bulk density of 0.28 g / mL, and an electrical resistivity of 8.91 × 10 6 was Ω·m
[0078] Measurement example 8 g of the gallium nitride powder obtained in Examples 4 and 5 and Comparative Examples 1 and 2 was weighed out, filled into a 10×40 mm rectangular parallelepiped mold, and molded into a molded body by uniaxial pressing at a pressure of 100 MPa, and the measured density and flexural strength were measured. The results are shown in the table below.
[0079] [Table 1]
[0080] From the powder of the example, 4.0 g / cm 3 It was confirmed that a molded body having a high measured density of 10 ...
Claims
1. A gallium nitride powder having an oxygen content of 0.5 at% or less, and having an electrical resistivity of 1.0×10 when 8 g of the powder is filled into a rectangular parallelepiped mold of 10 mm×40 mm and uniaxially pressed at a pressure of 100 MPa. 7 Gallium nitride powder having a resistivity of Ω·cm or less.
2. The powder according to claim 1 , wherein the gallium nitride is gallium nitride having nitrogen deficiencies.
3. 3. The powder according to claim 1 or 2, having a loose bulk density of 1.00 g / mL or more and 1.85 g / mL or less.
4. 3. The powder according to claim 1 or 2, having an average particle size of 1 μm or more and 150 μm or less.
5. 3. The powder according to claim 1, wherein the ratio of the 10% area diameter to the 90% area diameter is 0.01 or more and 0.45 or less.
6. The method for producing the powder according to claim 1, further comprising a heat treatment step of heat treating the gallium nitride powder at 900° C. or higher and 1300° C. or lower in an inert gas flow atmosphere.
7. The method according to claim 6, wherein the gallium nitride powder is gallium nitride powder obtained by nitriding metal gallium.
8. The method according to claim 6 or 7, wherein the inert gas flow atmosphere is an atmosphere in which a gas containing at least one of argon and nitrogen is flowed.
9. The method according to claim 6 or 7, wherein the flow rate of the inert gas is 500 mL / min or more and 5000 mL / min or less.
10. A method for producing a gallium nitride sintered body, comprising: a step of forming the powder according to claim 1 or 2 into a molded body; and a step of sintering the molded body.
